EFFECTIVENESS OF NUTRITIONAL COUNSELING USING BOOKLET AND LEAFLET ON DIET COMPLIANCE AND KNOWLEDGE LEVEL OF TYPE 2 DIABETES MELLITUS PATIENTS AT MEURAXA HOSPITAL, BANDA ACEH CITY - Ayu Afrilia; Safrida; Teuku Muliadi; Suci Eka Putri (PT. Radja Intercontinental Publishing, 2023)
Diabetes Mellitus (DM) is a chronic disease in the form of a metabolic disorder characterized by an increase in blood glucose levels above normal. Currently Aceh is in 8th place with the highest incidence of DM in Indonesia with the city with the highest incidence of DM being the city of Banda Aceh at 2.3%. Nutrition counseling for DM sufferers is providing education and understanding regarding knowledge and skills in controlling DM. Education is included in the 4 pillars of DM control so that it can increase patient knowledge regarding dietary compliance and prevent complications. The aim of this research was to determine the effectiveness of nutritional counseling using booklets and leaflets on dietary compliance and the level of knowledge of type 2 DM patients at Meuraxa Regional Hospital, Banda Aceh City. This research is a Quasi Experimental Design research using Pre-Post Test on booklet and leaflet groups. The sample used was 60 type 2 DM patients in classes II and III at Meuraxa Regional Hospital, Banda Aceh City, with 30 booklet groups and 30 leaflet groups. Statistical tests use Paired Sample T - Test and Independent Sample T – Test. This research shows that the results of nutritional counseling on dietary compliance posttest booklet are more effective than posttest leaflet, with a value of sig. (2-tailed) shows a P Value of 0.048. (p < 0.05). Nutrition counseling on the posttest booklet knowledge level is more effective than the leaflet posttest, with a sig. (2-tailed) shows a P Value of 0.045. (p < 0.05). So it can be concluded that providing nutritional counseling using booklets is more effective than leaflets on diet compliance and the level of knowledge of Type 2 DM patients at Meuraxa Regional Hospital, Banda Aceh City. Thus, nutritional counseling using booklet media is a recommendation for dietary compliance and the level of knowledge of type DM patients at Meuraxa Regional Hospital, Banda Aceh City.